Incentives and Workers' Motivation in the Public Sector - Josse Delfgaauw; Robert Dur (Tinbergen Institute, 2004)
Civil servants have a reputation for being lazy. However, people's personal experiences with civil servants frequently run counter to this stereotype. We develop a model of an economy in which workers differ in laziness and in public service motivation, and characterise optimal incentive contracts for public sector workers under different informational assumptions. When civil servants' effort is unverifiable, lazy workers find working in the public sector highly attractive and may crowd out dedicated workers. When effort is verifiable, a cost-minimising government optimally attracts dedicated workers as well as the economy's laziest workers by offering separating contracts, which are both distorted.
Keywords: H1; J3; J4; L3; M5; 330; Public Sector Labour Markets; Incentive Contracts; Work Ethics; Public Service Motivation; Öffentlicher Dienst; Leistungsanreiz; Anreizvertrag; Leistungsmotivation; Arbeitsethik; Theorie; Niederlande